PENERAPAN SISTEM TRANSFORMASI DIGITAL-ANDRAGOGI MELALUI MEDIA GOOGLE SITES PADA KELOMPOK KERJA PENYULUH AGAMA HINDU DENPASAR TIMUR KEMENTERIAN AGAMA KOTA DENPASAR - Kadek Dwi Sentana Putra Dwi Sentana Putra (UHN IGB Sugriwa Denpasar, 2022)
The East Denpasar Hindu Extension Working Group is a working team from the Ministry of Religious Affairs of Denpasar City that provides counseling to the community in the East Denpasar region, through the Sad Dharma method and through the Google Sites application owned today. Sad Dharma is a form of service to the community through the extension of Hinduism with the approach of the pattern of